Cost-effectiveness analysis of cabozantinib plus atezolizumab for advanced hepatocellular carcinoma - Zhu, Yan; He, Cheng; Cao, Shi-Chao; Li, Hui-Jun; Cai, Ru-Xue; Bai, Zhao-Jun; Xia, Tong-Xia (Frontiers in Pharmacology, 2025)
BackgroundCabozantinib combined with atezolizumab has been shown to prolong progression-free survival in first-line treatment of advanced hepatocellular carcinoma (HCC). However, the cost-effectiveness of this regimen remains unknown. This study aimed to evaluate the cost-effectiveness of cabozantinib plus atezolizumab compared with sorafenib for first-line treatment of advanced HCC from the perspectives of the Chinese health system and the US payers.MethodsA partitioned survival model was constructed based on a phase III randomized clinical trial (COSMIC-312) to compare the health benefits and economic outcomes of cabozantinib plus atezolizumab versus sorafenib for the treatment of hepatocellular carcinoma. Costs and utilities were obtained from published literature. Data recorded included quality-adjusted life years (QALYs), life years (LYs), and incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were conducted to test the robustness of the results. Subgroup analyses were also performed.ResultsFrom the perspectives of the US payers and the Chinese health system, the base-case ICER values for cabozantinib plus atezolizumab compared to sorafenib were $-2,731,994.74/QALY and $-2,225,520.14/QALY, respectively. Sorafenib achieved an absolute dominance in terms of cost-effectiveness, offering greater benefits at a lower cost. The models were most sensitive to the utility values for progression-free survival and overall survival. Subgroup analyses also demonstrated that cabozantinib plus atezolizumab was unlikely to be cost-effective as a first-line treatment for advanced HCC.ConclusionCabozantinib plus atezolizumab was not a cost-effective treatment option for HCC when compared to sorafenib from both the Chinese healthcare system and the US payer perspectives.